PENGELOLAAN WAKAF TUNAI: STUDI KASUS PADA LEMBAGA LAZ AL-HILAL BANDUNG - Puji Lestari, Fitriyani; Ma’mun, Saepul; Setiadi (Jurnal Pelita Nusa, 2024)
In 2019, the Indonesian Waqf Board (BWI) recorded the potential of waqf assets in Indonesia reaching 2000 trillion rupiah per year with a waqf land area of 420,000 hectares. However, most of the waqf land is used for worship sectors such as mosques and prayer rooms, while other sectors such as education, social, and economic are still minimal. The low public understanding of productive waqf is an obstacle to increasing the active participation of the community in the world of waqf. This study aims to evaluate the management of cash waqf at LAZ Al-Hilal Bandung, as well as explore steps to increase its distribution to support the welfare of the people. This research uses a qualitative approach with interview, observation, and documentation techniques. The validity of the data is checked through source triangulation. The analysis was carried out through data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that the management of cash waqf at LAZ Al-Hilal has gone quite well and provided benefits. However, there is a weakness in the socialization aspect, where the lack of counseling and information about cash waqf leads to low public knowledge about this program and access to information through the LAZ Al-Hilal website.